China’s Ice Securitization - Asya Gasparyan; Paulo Afonso B. Duarte (China Quarterly of International Strategic Studies, 2025)
Given the scarce number of studies on China’s presence and intentions in Antarctica compared to other remote regions, such as the Arctic, this paper draws on securitization theory to demonstrate that, despite China’s discursive efforts to legitimize its Antarctic initiatives through the altruistic narrative of scientific exploration and the protection of the global commons, China’s securitization of the South Pole follows a different approach. In fact, it conceals a realist agenda that includes building and consolidating its presence, biding its time, and ultimately exploiting the region’s resources. China is aware that, in 2048, the treaty system that prevents the exploitation of the region will expire. Thus, although silent and discreet, China’s securitization of Antarctica has been making significant progress, not only through an increasing number of polar bases but also by assigning Chinese names to new geographical locations, and establishing a Chinese air squadron in the South Pole, among other revisionist actions.